Flow behavior and physicochemical characterization of peach pulps (Scientia Agropecuaria, 2012)
Rheological and physicochemical analyses were conducted on nine varieties of peach pulps from Mendoza (Argentina) at a range of soluble solids concentration (12.5 to 28°Brix) and temperatures (30 to 50°C).The rheology of the pulps followed the power law model for all conditions, behaving as pseudoplastic fluids. Rheological: consistency coefficient and flow behavior index, using a rotational type viscometer and physicochemical parameters (methods proposed by AOAC): soluble solids, pH, water content, insoluble solids, acidity and pectin content (refractometric method) were determined in this study. Cluster analysis established two groups (1: Halford, Andross, Astengo, Bowen, Sim’s Cling; 2: Fortuna, Loadel and Palora; Sullivan Cling variety could not be assigned to any group) with significant differences.
Keywords: Rheology; peach pulp; physicochemical properties; soluble solids; temperature; power law; pseudoplastic.